Unique phenotypes and clonal expansions of human CD4 effector memory T cells re-expressing CD45RA. Issue 1 (December 2017) - Tian, Yuan; Babor, Mariana; Lane, Jerome; Schulten, Veronique; Patil, Veena; Seumois, Grégory; Rosales, Sandy; Fu, Zheng; Picarda, Gaelle; Burel, Julie; Zapardiel-Gonzalo, Jose; Tennekoon, Rashika; et al.
Abstract The expression of CD45RA is generally associated with naive T cells. However, a subset of effector memory T cells re-expresses CD45RA (termed TEMRA) after antigenic stimulation with unknown molecular characteristics and functions. CD4 TEMRA cells have been implicated in protective immunity against pathogens such as dengue virus (DENV). Here we show that not only the frequency but also the phenotype of CD4 TEMRA cells are heterogeneous between individuals. These cells can be subdivided into two major subsets based on the expression of the adhesion G protein-coupled receptor GPR56, and GPR56+ TEMRA cells display a transcriptional and proteomic program with cytotoxic features that is distinct from effector memory T cells. Moreover, GPR56+ TEMRA cells have higher levels of clonal expansion and contain the majority of virus-specific TEMRA cells. Overall, this study reveals the heterogeneity of CD4 TEMRA cells and provides insights into T-cell responses against DENV and other viral pathogens. Memory T cells are essential for combating recurring infection by promoting prompt and effective immune responses. Here the authors show, via system biology approaches, that human CD4 memory T cells contains a CD45RA-rexpressing pool that can be further subsetted by the expression of GPR56 for distinct functionalities.